Investigating the learning perspective of Searching as Learning, a review of the state of the art - Gimenez, Paulo Jose de Alcantara; Machado, Marcelo de Oliveira Costa; Pinelli, Cleber Pinelli; Siqueira, Sean Wolfgand Matsui (Anais do Simpósio Brasileiro de Informática na Educação (SBIE), 2020)
Current search engines are not designed to facilitate learning as they do not lead the user to develop more complex skills. Searching as Learning (SAL) emerged as a research area from the intersection of information search and learning technologies in order to advance the study of searching as a learning process. However, we wonder how have the learning theories and approaches been explored in SAL. Through a systematic review of the literature, we identified 65 papers that report SAL solutions. We analyzed them, seeking to answer (i) which learning theories, approaches and methods support the searching as a learning process, and (ii) what metrics, procedures, or treatments were used to measure learning during the searching process. We uncover the learning perspective in the SAL literature, discussing the learning paradigms, the mechanisms influencing the learning process, the search session design for learning and the knowledge gain measurement strategies.